RESPON MASYARAKAT DESA ADAT KUTA TERHADAP PROGRAM CORPORATE SOCIAL RESPONSIBILITY DI DISCOVERY KARTIKA PLAZA HOTEL - Abhicanika, I Putu Wiweka; Tamim, Imron Hadi; Ranteallo, Ikma Citra (JURNAL ILMIAH SOSIOLOGI (SOROT), 2016)
ABSTRACT   DKPH (Discovery Kartika Plaza Hotel) has become one of the company which awares implementing of CSR (Corporate Social Responsibility) for society and environment around of the company.  CSR has implementation base on community need, not to increase the quality of life like Badung’s regulation  about TJSP (Social Responsibility). Becuase people in Desa Adat Kuta have to capable. This study use a descriptive qualitative method which to see the society of Desa Adat Kuta response of CSR DKPH. And the method along to analyze the form of CSR program that have to implementation by DKPH. This study use observation, interview and document to collect data. Base on research have to conduct by Stakeholder Theory, CSR can be effective for communication tools to mantain the sustainability of the company in the middle of society. Company can stand in the middle of social life, if they listen to people society and  attention to planet (environment) surrounding the company. Keyword : DKPH CSR, public response, environment, Stakeholder theory.